IMPROVING LEARNING ACTIVITY AND LEARNING OUTCOMES OF ISLAMIC CULTURAL HISTORY THROUGH THE TWO STAY TWO STRAY STRATEGY - Ajeng Dwi Aditama; Pamungkas Stiya Mulyani; Faisal Kamal (Alphateach (Jurnal Profesi Kependidikan dan Keguruan), 2025)
One of the problems in education is the low quality of religion-based education, including in the subject of Islamic Cultural History. The use of learning strategies is a problem that is often faced so that it causes boredom and lack of interest. This study aims to determine the effect of using the Two Stay Two Stray strategy to increase learning activity and learning outcomes of Islamic Education. Data collection was carried out using two tests, namely pretest and posttest, observation, interviews, and documentation. In addition, to obtain data on learning activity, a questionnaire was used. The analysis used was descriptive analysis. In this study, the research subjects were class VI, totaling 13 students. The results obtained from the tests conducted show that the Two Stay Two Stray strategy has a good influence on improving the learning activity and learning outcomes of class VI students of MI Ma'arif Gesing Garung. The learning outcomes are proven based on the results of the test. From the calculation results obtained, the calculated value is greater than the table both at the significance level of 5% (14.1654 ˃ 2.1788) and 1% (14.1654 ˃ 3.0545). For learning activity, from the results of the questionnaire and observations conducted in the classroom, students experienced a fairly good increase in learning activity. iThe results of the questionnaire obtained the highest ipoint ipoint which 4 (SS) with an average value of 72.04.